HUKUM ARISAN ONLINE, ARISAN GUGUR, DAN ARISAN BARANG PERSPEKTIF K.H.MOCHYAR DAHRI - -, Dita Indah Lestari; Setyanoor, Erwan (LPPM STAI DARUSSALAM LAMPUNG, 2025)
This article examines the practice of arisan in various forms, including online arisan, gugur arisan, and goods-based arisan, from the perspective of Islamic law based on the views of K.H. Mochyar Dahri. The background of this study is the increasing popularity of technology-based arisan practices that have raised legal and ethical issues, requiring clarification from a sharia perspective to ensure compliance with Islamic commercial principles. This research employs a qualitative method with a descriptive approach, using field data collection techniques through in-depth interviews and documentation of relevant literature. The aim is to describe and analyze the legal status of each type of arisan in light of Islamic principles such as justice, transparency, and public benefit. The findings indicate that each form of arisan has a different legal status depending on the clarity of the contract, mutual agreement, and the avoidance of gharar (uncertainty), riba (interest), and maysir (gambling). Online arisan is permissible if it avoids prolonged use of conventional banking systems. Gugur arisan is valid if there is mutual consent from the outset. Goods-based arisan, however, tends to be problematic due to price fluctuations. In conclusion, arisan is permissible when it follows sharia principles. This study contributes to contemporary Islamic legal literature on digital socio-economic practices.